CRISPR-Cas9 Editing of Human Histone Deubiquitinase Gene USP16 in Human Monocytic Leukemia Cell Line THP-1 - Gažová, Iveta; Lefevre, Lucas; Bush, Stephen J.; Rojo, Rocio; Hume, David A.; Lengeling, Andreas; Summers, Kim M. (Frontiers in Cell and Developmental Biology, 2021)
USP16 is a histone deubiquitinase which facilitates G2/M transition during the cell cycle, regulates DNA damage repair and contributes to inducible gene expression. We mutated the USP16 gene in a high differentiation clone of the acute monocytic leukemia cell line THP-1 using the CRISPR-Cas9 system and generated four homozygous clones. All were able to proliferate and to differentiate in response to phorbol ester (PMA) treatment. One line was highly proliferative prior to PMA treatment and shut down proliferation upon differentiation, like wild type. Three clones showed reduced proliferation prior to differentiation, with sustained expression of the progenitor cell marker MYB, indicating that differentiation had not completely blocked proliferation in these clones. Network analysis of transcriptomic differences among wild type, heterozygotes and homozygotes showed clusters of genes that were up- or downregulated after differentiation in all cell lines. Prior to PMA treatment, the homozygous clones had lower levels than wild type of genes relating to metabolism and mitochondria, including SRPRB, encoding an interaction partner of USP16. There was also apparent loss of interferon signaling. In contrast, a number of genes were upregulated in the homozygous cells compared to wild type at baseline, including other deubiquitinases (USP12, BAP1 and MYSM1). However, three homozygotes failed to fully induce USP3 during differentiation. Other network clusters showed effects prior to or after differentiation in the homozygous clones. Thus the removal of USP16 affected the transcriptome of the cells, although all these lines were able to survive, which suggests that the functions attributed to USP16 may be redundant. Our analysis indicates that the leukemic line can adapt to the extreme selection pressure applied by the loss of USP16, and the harsh conditions of the gene editing and selection protocol, through different compensatory pathways. Similar selection pressures occur during the evolution of a cancer in vivo, and our results can be seen as a case study in leukemic cell adaptation. USP16 has been considered a target for cancer chemotherapy, but our results suggest that treatment would select for escape mutants that are resistant to USP16 inhibitors.